2023
DOI: 10.1038/s41598-023-36508-3
|View full text |Cite
|
Sign up to set email alerts
|

Induced pluripotent and CD34+ stem cell derived myeloid cells display differential responses to particle and dust mite exposure

Abstract: Myeloid cells form an essential component of initial responses to environmental hazards and toxic exposures. The ability to model these responses in vitro is central to efforts tasked with identifying hazardous materials and understanding mechanisms of injury and disease. Induced pluripotent stem cell (iPSC) derived cells have been suggested as alternatives to more established primary cell testing systems for these purposes. iPSC derived macrophage and dendritic like cells were compared to CD34+ haematopoietic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 74 publications
(80 reference statements)
0
0
0
Order By: Relevance
“…Building from this work in our current study, we have used Scseq to further characterise the different cell types within these in vitro systems and tested how some of them respond to HDM exposure. Again, building on previous work, where we demonstrated that CD34+ derived macrophages respond to particle and house dust mite exposures through an increase in inflammatory mediators including CXCL5, CCL15 and metallothionein MT1M expression 24 , our aim in this study was to identify the cell types responsible for these changes in gene expression. Ultimately, through the identification of MNP cell types, which are highly responsive to environmental stimuli, and present within diseased airways, one can help refine mechanistic understanding of how inhaled exposures contribute to exacerbation of disease conditions such as allergic asthma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Building from this work in our current study, we have used Scseq to further characterise the different cell types within these in vitro systems and tested how some of them respond to HDM exposure. Again, building on previous work, where we demonstrated that CD34+ derived macrophages respond to particle and house dust mite exposures through an increase in inflammatory mediators including CXCL5, CCL15 and metallothionein MT1M expression 24 , our aim in this study was to identify the cell types responsible for these changes in gene expression. Ultimately, through the identification of MNP cell types, which are highly responsive to environmental stimuli, and present within diseased airways, one can help refine mechanistic understanding of how inhaled exposures contribute to exacerbation of disease conditions such as allergic asthma.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we used human primary bone marrow derived CD34+ stem cells to generate different populations of MNPs, found within inflammatory airway disease, with the aim to test responses to pollutant particulate and allergen exposure 23 , 24 . These stem cells give rise to many if not all of the infiltrating MNP cells in allergic and asthmatic lung disease and have also been observed to replace alveolar macrophages 25 as they are depleted from the lung in disease.…”
Section: Introductionmentioning
confidence: 99%